Answer:
w
Step-by-step explanation:
Answer:
x^2 + 18x + 76 + 5 = 0 + 5
Step-by-step explanation:
The first step is to determine the constant that is needed to be able to write the expression in the desired form. That constant is the square of half the x-term coefficient: (18/2)^2 = 9^2 = 81.
The constant that is present is 76, which is 5 fewer than the needed constant, so the "first step" is to add 5 to both sides of the equation:
x^2 + 18x + 76 + 5 = 0 + 5
Then the next step would be to write the left side as a square:
(x +9)^2 = 5 . . . . . . . p = -9; q= 5
Answer:
n°
Step-by-step explanation:
Your selection is correct. Once again, they are alternate angles, meaning they're equal to one another.